A temporal perspective on the relationship between top management team internationalization and firms' innovativeness - Michaela Wrede; Tobias Dauth (Managerial and Decision Economics, 2020)
This study examines whether top management team (TMT) internationalization is positively related to firm innovativeness. Besides focusing on the accumulation of top managers' international knowledge and capabilities, we explore the influence of moderators reflecting temporal concerns at three levels: CEO age, TMT tenure, and firm age. Combining upper echelons theory with innovation literature and using a sample of large stock-listed German firms, we demonstrate that TMT internationalization can increase firm innovativeness. This relationship is context-dependent on the age of the CEO. Overall, this paper sheds light on the antecedents of firm innovativeness and the consequences of increasingly international TMTs.
Keywords: 650